Physicochemical characterization of agricultural by-products: case of the peelings of varieties of yams produced in Côte d’Ivoire: Agricultural by-products and nutritional value - Kouadio, Irène Ahou (European Journal of Applied Sciences, 2021)
In this study, the physicochemical characteristics of the peelings of three varieties of yam commonly called "Bètè Bètè". "Krenglè" and "Kponan" which are the most consumed in Côte d'Ivoire were evaluated in order to contribute to the determination of the nutritional value of this fraction of these yams which is very often thrown away as household waste. Known standard methods were used for this physicochemical characterization. The results obtained show that the peelings of the variety "Kponan" are the richest in fat (2.33% ± 0.02), carbohydrates (82.95% ± 0.02) and fiber (1.58 % ± 0.01). On the other hand, the highest proteins content (8.05% ± 0.1) was observed in those of the variety “Bètè Bètè”. This protein content is also higher than those observed in the flesh of yams. For major minerals such as magnesium and iron, the highest levels were observed in the peelings of the variety “Krenglè”. Those of the variety “Kponan” are the richest in potassium. On the other hand, the peelings of the variety “Bètè Bètè” are the richest in calcium. These yam’s peelings could thus be transformed for use in times of scarcity to fight against Hunger.